A Case Report on Agoraphobia with Panic Disorder Manifesting after Traumatic Brain Injury - Suprakash Chaudhury; Gagandeep Singh; Swaleha Mujawar; Tahoora Ali; Daniel Saldanha (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
Traumatic Brain Injury (TBI) is a major cause of death and disability all over the globe. Almost 50% of the victims of TBI are subsequently diagnosed with psychiatric disorders. Psychiatric disorders are not uncommon following TBI since the parts of the brain most susceptible to damage from trauma are the frontal and the parietal lobes, which are also known to be the location of most psychiatric disorders. The emergence of anxiety disorder following a TBI is poorly understood and largely unexplored. The purpose of this study was to report a case of a patient who developed agoraphobia with panic disorder after a TBI for an extended period of time. The condition of a 60-year-old male patient who developed panic disorder with agoraphobia after traumatic brain injury is reported and explained briefly. The reported case suggests that TBI can cause long-term psychiatric disorders in some people, emphasising the importance of psychiatric follow-up for all TBI patients.